1990
DOI: 10.1165/ajrcmb/2.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Heparan Sulfate Proteoglycan. I. Inhibitory Effects on Smooth Muscle Cell Proliferation

Abstract: Proliferation of smooth muscle cells is an important component of pulmonary arterial morphogenesis, both during normal development and pathologic remodeling. However, little is known of the factors that regulate smooth muscle proliferation in these vessels. To investigate the hypothesis that factors produced by endothelial cells may regulate smooth muscle cell growth, we studied the effects of culture medium conditioned by fetal bovine pulmonary arterial endothelium on proliferation of smooth muscle cells in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 53 publications
2
43
0
Order By: Relevance
“…Perlecan is widely expressed in the basement membranes of adult tissues and in all vascular structures (Couchman, 1987;Murdoch et al, 1994) and has been directly implicated as a potent endothelial cell-derived inhibitor of SMC replication (Benitz et al, 1990). Our data indicate that at least some of the gene-regulating activity of perlecan resides in its heparan sulfate side chains, consistent with a large body of evidence implicating heparin-like molecules in the regulation of various SMC functions (Clowes and Karnovsky, 1977;Castellot et al, 1981;Majack and Bornstein, 1984;Majack and Clowes, 1984;Marcum and Rosenberg, 1984;Majack et al, 1985;Fritze et al, 1985;Benitz et al, 1990;Campbell et al, 1992;Pukac et al, 1992;Au et al, 1993).…”
Section: Role Of Basement Membrane Components Insupporting
confidence: 83%
See 2 more Smart Citations
“…Perlecan is widely expressed in the basement membranes of adult tissues and in all vascular structures (Couchman, 1987;Murdoch et al, 1994) and has been directly implicated as a potent endothelial cell-derived inhibitor of SMC replication (Benitz et al, 1990). Our data indicate that at least some of the gene-regulating activity of perlecan resides in its heparan sulfate side chains, consistent with a large body of evidence implicating heparin-like molecules in the regulation of various SMC functions (Clowes and Karnovsky, 1977;Castellot et al, 1981;Majack and Bornstein, 1984;Majack and Clowes, 1984;Marcum and Rosenberg, 1984;Majack et al, 1985;Fritze et al, 1985;Benitz et al, 1990;Campbell et al, 1992;Pukac et al, 1992;Au et al, 1993).…”
Section: Role Of Basement Membrane Components Insupporting
confidence: 83%
“…The protein core consists of five distinct molecular domains, including a perlecan-specific domain containing heparan sulfate attachment sites and domains homologous with the low-density lipoprotein receptor, the laminin A globular region, immunoglobulin repeats, and epidermal growth factor-like repeats (Noonan et al, 1991;Noonan and Hassell, 1993;lozzo et al, 1994). Perlecan is widely expressed in the basement membranes of adult tissues and in all vascular structures (Couchman, 1987;Murdoch et al, 1994) and has been directly implicated as a potent endothelial cell-derived inhibitor of SMC replication (Benitz et al, 1990). Our data indicate that at least some of the gene-regulating activity of perlecan resides in its heparan sulfate side chains, consistent with a large body of evidence implicating heparin-like molecules in the regulation of various SMC functions (Clowes and Karnovsky, 1977;Castellot et al, 1981;Majack and Bornstein, 1984;Majack and Clowes, 1984;Marcum and Rosenberg, 1984;Majack et al, 1985;Fritze et al, 1985;Benitz et al, 1990;Campbell et al, 1992;Pukac et al, 1992;Au et al, 1993).…”
Section: Role Of Basement Membrane Components Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, perlecan has been shown to inhibit thrombosis and intimal hyperplasia after arterial injury (153). Several studies have shown that endothelialderived perlecan is a potent inhibitor of SMC proliferation in vitro (149,154,155). Perlecan binds to heparin-binding mitogens such as FGF-2, leading to inactivation of FGF-2, a potent stimulatory growth factor, due to its heparin-binding property.…”
Section: Perlecanmentioning
confidence: 99%
“…This action is multifactorial, including an inhibition of mitogens in plasma, inhibition of excretion of platelet-derived growth factor (PDGF), interference with thrombin mitogenic activity, deliberation of cell-bound thrombospondin (free thrombospondin is unable to interact with PDGF) (Majack, 1985(Majack, , 1986(Majack, , 1988, inhibition of DNA synthesis in smooth muscle cells by intracellular heparin (Reilly et al, 1986;Wright et al, 1989), heparin-dependent inhibition of VSMC protein synthesis Cochran et al, 1985) and protecting of heparan sulphate from biodegradation by heparinase released from platelets (Fritz et al, 1985;Castellot et al, 1987;Wright et al, 1989). In the last case, the following events have been observed: (1) both heparin and heparan sulphate inhibit VSMC growth in a similar fashion (Castellot et al, 1981(Castellot et al, , 1987Benitz et al, 1990), endothelial cells synthesize heparan sulphate in the same manner as smooth muscle cells; (2) smooth muscle cells synthesize heparan sulphate more during continuous growth than during growth on exponential cell-lines (Fritz et al, 1985); (3) media containing heparan sulphate (those fixed by heparinase from flavobacteria) increase the sensitivity of VSMC's to various mitogens and growth stimulators (Castellot et al, 1981). Heparinase itself can be released by internal platelet and monocyte activation (Oldberg et al, 1980;Castellot et al, 1982;Wright et al, 1989).…”
Section: Effect Of Heparin On Vascular Smooth Muscle Cell Proliferationmentioning
confidence: 98%